Uncovering Determinant of Anaemia Among Adolescent Girls - Taqwin, Taqwin; Amsal, Amsal; Batjo, Siti Hadijah; Radhiah, Siti; Ramadhan, Kadar; Kusumawati, Dwi Erma; Hafid, Fahmi; Hariadha, Enti; Ahmed, Faiz; Raju, Kaveesha (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Anaemia is a significant global public health issue that primarily affects adolescent girls. Smoking, malaria, and low family income are associated with teenage Anaemia in girls. The purpose of the study was to uncover determinant Anaemia among adolescent girls. This type of research is cross-sectional. The research location was at the high schools in Central Sulawesi from March to September 2023. The study sample was teenage girls, with as many as 384 respondents. Simple random sampling was the method used for the sample. The study's independent variables included the respondents' anthropometrics, sociodemographics, and infectious illnesses. The dependent variable was haemoglobin levels. The research instrument used a Kobotoolbox application questionnaire. They measure weight with digital scales, height with Length board measuring, and arm circumference with mid-upper arm circumstances. Laboratory analysts carried out measurements of haemoglobin levels. Chi-square test analysis of research data with a 95% confidence level. Test of logistic regression in multivariate analysis. The findings indicated that 20.3% of teenage girls suffered from Anaemia. Adolescent girls who smoke (OR=3.2, 95% CI (1.10, 8.70)), have malaria (OR=1.9, 95% CI (0.80, 5.00)), and come from an income family with less than Rp. 2.599.546 (OR=1.7, 95% CI (1.00, 2.90)) are at risk for Anaemia. Adolescent girls' anaemia prevalence was a moderate public health concern. Teenage girls who smoke, have malaria and have a family low income below are determinants for Anaemia.